Third time’s a charm: reviewing the advertisement call of Gabohyla pauloalvini (Anura: Hylidae: Scinaxinae), an endemic species from Brazil’ Atlantic Forest - Carmo, Luiz Fernando; Alves, Juliana; Dias, Iuri R.; Solé, Mirco; de Mira-Mendes, Caio V.; Santos, Laisa; Júnior, Mário Barbosa S.; Zocca, Cássio; Ferreira, Rodrigo B.; Lacerda, João Victor A. (Zootaxa, 2021)
The Neotropical tribe Sphaenorhynchini is composed of 15 recognized species commonly named as “lime treefrogs”. Gabohyla pauloalvini occurs in Atlantic Forest lowlands through the states of Bahia and Espírito Santo, Brazil. Based on field observation, literature review, and evaluation of audio files, we conclude that previous bioacoustic descriptions were erroneously assigned to G. pauloalvini. Here, we describe for the first time the advertisement call of G. pauloalvini from two disjunct populations. In addition, we provide new distribution records and an updated map for this species. The advertisement call of G. pauloalvini is composed of 1–5 closely spaced notes, with duration of 0.016–1.976 s, inter-note intervals of 0.340–1.25 s, and an average dominant frequency (= fundamental frequency) of 4966.0 Hz. Harmonics are visible in the spectrogram. Three new populations of G. pauloalvini have been recorded and extended the distribution by 60 km south. Nevertheless, G. pauloalvini is still known only from few localities. We highlight the importance of depositing audio recordings and specimens in scientific collections to promote systematics and natural history studies.